2021
DOI: 10.3389/fpsyt.2021.608317
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Roles of Emotional Regulation on Negative Emotion and Internet Addiction Among Chinese Adolescents From a Development Perspective

Abstract: Previous researches indicated that emotional regulation can be associated with depression and anxiety, which may be an important mediating factor between emotional regulation and internet addiction. However, the mechanism between these associations has received little attention and it is still unclear. This study has examined 716 Chinese adolescents, 341 were males (47.6%), aged 13 to 18(Mean = 14.58, SD = 1.50), using a cross-sectional survey involving Young's Diagnostic Questionnaire for Internet Addiction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 60 publications
3
8
0
Order By: Relevance
“…The following is an example item: “During COVID-19, have you tried many times to control or stop surfing the Internet without success?”. The scale has also shown good reliability and validity in other studies ( Liang et al, 2021 ), and the Cronbach's alpha for this study was 0.85.…”
Section: Methodssupporting
confidence: 73%
“…The following is an example item: “During COVID-19, have you tried many times to control or stop surfing the Internet without success?”. The scale has also shown good reliability and validity in other studies ( Liang et al, 2021 ), and the Cronbach's alpha for this study was 0.85.…”
Section: Methodssupporting
confidence: 73%
“…69,70 A meta-analysis also supports this relationship by demonstrating that lower levels of reappraisal are associated with higher levels of depression with a small-to-moderate effect size. 71 Secondly, this study replicated previous findings that healthy individuals use more reappraisal in low-intensity situations but more distraction in high-intensity situations regardless of stimulus valence. 38,64,72 And a similar trend was also found in the IA group.…”
Section: Discussionsupporting
confidence: 87%
“…69,70 A meta-analysis also supports this relationship by demonstrating that lower levels of reappraisal are associated with higher levels of depression with a small-to-moderate effect size. 71…”
Section: Discussionmentioning
confidence: 99%
“…The second hypothesis (H2) was also confirmed: the mediation model showed a direct effect of emotional (dys)regulation on IA, suggesting that emotional regulation may play an important role in the development of IA. Indeed, studies have shown that individuals with IA—especially adolescents—have greater difficulties with emotional regulation, resulting from excessive suppression and poor cognitive reappraisal [ 47 , 103 , 104 ]. The excessive suppression of negative emotional experiences involved in emotional dysregulation may strengthen its correlation with IA.…”
Section: Discussionmentioning
confidence: 99%